Myocardial ischemia and reperfusion: direct evidence for free radical generation by electron spin resonance spectroscopy. - Baker, J E (1988)
Electron spin resonance spectroscopy has recently been used by others to detect directly radical species in isolated perfused hearts. Sample processing prior to spectroscopy in this study involved pulverization of tissue, which can artifactually generate radical species. We assessed in isolated perfused hearts the influence of tissue pulverization on the identity of radical species detected by spectroscopy and then, using a processing technique less likely to induce artifacts, whether myocardial ischemia and reperfusion generate radical species. Rat and rabbit hearts (n = 8) were perfused aerobically for 10 min and freeze-clamped to -196 degrees C. Frozen tissue was processed at -196 degrees C for spectroscopic analysis by pulverization vs. chopping. Spectra of pulverized tissue consisted of three components: a semiquinone (g = 2.004), a lipid peroxy radical (g [ = 2.04 and g = 2.006), and a carbon-centered radical that is possibly a lipid radical (giso = 2.002 and AHzz approximately equal to 50 G). Chopped tissue consisted of a single component, a semiquinone (g = 2.004). Rat hearts (n = 8 per group) also underwent 10-min global no-flow normothermic ischemia followed by 5-60 sec of either aerobic or anaerobic reperfusion, with frozen tissue chopped prior to spectroscopy. Spectra of ischemic tissue consisted of an iron-sulfur center and a semiquinone. Aerobic reperfusion resulted in a spectrum similar to the control but with increased amplitude that peaked after 10-15 sec of reflow. Anaerobic reperfusion yielded a spectrum identical to that of ischemic tissue. We conclude that pulverization of frozen myocardial tissue arti-factually generates radical species. Using a nonpulverization technique for tissue processing, we found that myocardial ischemia and reperfusion produce radical species but that molecular oxygen is necessary for the burst of radical production during reflow.